Monitoring of the content of toxic substances in different vegetables widen in Ukraine - Dubinina, Antonina (Eastern-European Journal of Enterprise Technologies, 2012)
Monitoring of the content of nitrates, radionuclides, salts of heavy metals in different botanical sorts of potatoes, beetroots, tomatoes, onions, carrots, pumpkin has been performed. The received data allow us state the presence of spatial and varietal specifics of the level of accumulating toxicants. The researched plants can be placed in the following order according to the level of accumulating nitrates in productive organs: tomatoes < onion < carrot < pumpkin < potatoes < beetroot. All researched samples of vegetables accumulate cesium more than strontium. It is determined that not only spatial but varietal divergence by the level of accumulating radioactive isotopes of strontium and cesium are observed in the vegetables under research. Heavy metals can be placed in the following order by the level of accumulation: zinc > copper > lead > cadmium.